Predictors of Hospital Mortality and the Related Burden of Disease in Severe Traumatic Brain Injury: A Prospective Multicentric Study in Brazil - Areas, Fernando Zanela; Schwarzbold, Marcelo Liborio; Diaz, Alexandre Paim; Rodrigues, Igor Kunze; Sousa, Daniel Santos; Ferreira, Camila Leite; Quevedo, João; Lin, Katia; Kupek, Emil; Ritter, Cristiane; Dal Pizzol, Felipe; Walz, Roger (Frontiers in Neurology, 2019)
Traumatic brain injury (TBI) is a worldwide social, economic and health problem related to premature death and long-term disabilities. There were no prospective and multicentric studies analysing the predictors of TBI related mortality and estimating the burden of TBI in Brazil. To address this gap, we investigated prospectively: 1) the hospital mortality and its determinants in patients admitted with severe TBI we analyzed in three reference centers; 2) the burden of TBI estimated by the years of life lost (YLLs) due to premature death based on the hospital mortality considering the hospital mortality. Between April 2014 and January 2016 (22 months), all the 266 patients admitted with Glasgow coma scale (GCS), ≤ 8 admitted in three TBI reference centers were included in the study. These centers cover a population of 1,527,378 population of the Santa Catarina state, Southern Brazil. Most patients were male (n = 230, 86.5%), with a mean (SD) age of 38 (17) years. Hospital mortality was 31.1% (n = 83) and independently associated with older age, worse cranial CT injury by the Marshall classification, the presence of subarachnoid hemorrhage in the CT, lower GCS scores and abnormal pupils at admission. The final multiple logistic regression model including these variables showed an overall accuracy for hospital mortality of 77.9% (specificity 88.6%, sensitivity 53.8%, PPV 67.7%, and NPV 81.1%). The estimated annual incidence of hospitalizations and mortality due to severe TBI were 9.5 cases and 5.43 per 100,000 inhabitants respectively. The estimated YLLs in 22 months, in the 2 metropolitan areas were 2,841, corresponding to 1,550 YLLs per year and 101.5 YLLs per 100,000 people every year. The hospital mortality did not change significantly since the end of the 1990s and was similar to other centers in Brazil and Latin America. Significant predictors of hospital mortality were the same as those of studies worldwide, but their strength of association seemed to differ according to countries income. Present study results question the extrapolation of TBI hospital mortality models for high income to lower- and middle-income countries and therefore have implications for TBI multicentric trials including countries with different income levels.